The security analysis of E91 protocol in collective-rotation noise channel. (May 2018) - Li, Leilei; Li, Hengji; Li, Chaoyang; Chen, Xiubo; Chang, Yan; Yang, Yuguang; Li, Jian
The bit error in quantum communication is mainly caused by eavesdropping and noise. However, most quantum communication protocols only take eavesdropping into consideration and ignore the result of noise, making the inaccuracy situations in detecting the eavesdropper. To analyze the security of the quantum E91 protocol presented by Ekert in collective-rotation noise channel, an excellent model of noise analysis is proposed. The increment of the qubits error rate (ber) is used to detect eavesdropping. In our analysis, eavesdropper (Eve) can maximally get about 50% of the key from the communication when the noise level approximates to 0.5. The results show that in the collective-rotation noise environment, E91 protocol is secure and the raw key is available just as we have knew and proved. We also presented a new idea in analyzing the protocol security in noise channel.